A post-occupancy evaluation of the Hope City Housing Complex of the Greater Middelburg Housing Association, Mpumalanga - Moja, Bontlefeela (Stellenbosch : Stellenbosch University, 2012)
Thesis (M Cosumer Science)--Stellenbosch University, 2004.